Comparative Analysis of Certification Organic and Non-Organic Rice Farming Income in East OKU District - Masroka, B; Sari, Fifian Permata; Sari, Y (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2024)
East OKU Regency is the second-largest rice-producing region in South Sumatra, following Banyuasin Regency, with a harvest area of 108,140.86 hectares in 2022. In recent years, the cultivation of certified organic rice has been developed in East OKU, particularly in East Buay Madang District and Belitang II District. These areas began developing organic rice in 2016 and received organic certification from INOFICE in 2020. This study examines the income differences between organic and non-organic rice farmers in East OKU Regency. The research was conducted in January 2024 in East OKU Regency using a survey method and disproportionate stratified random sampling. The sample consisted of 30 organic rice farmers out of 97 and 30 non-organic rice farmers out of 175 in Belitang Mulya District. Data analysis involved using an income equation to calculate farmers' income and the t-student test to determine the income differences between organic and non-organic rice farmers. The results show that the income of certified organic rice farmers in East OKU Regency is IDR 28,791,050 per hectare per year, or IDR 48,758,30 per hectare per year, which is significantly higher than the income of non-organic rice farmers, who earn IDR 11,334,887 per hectare per year, or IDR 24,574,281 per hectare per year. The difference in income between certified organic and non-organic rice farming in East OKU Regency is IDR 17,456,163 per hectare per year, or IDR 24,184,022 per hectare per year.